Realcalinização eletroquímica de matrizes cimentícias carbonatadas: influência do tempo e da densidade de corrente elétrica - Rachadel, Ana Carolina (2021)
In urban environments, rebar corrosion of reinforced concrete structures is mainly caused by the carbonation process due to a high concentration of carbonic gas released into the atmosphere. Carbonation occurs when CO2 enters the concrete structure and reacts with alkaline products, causing a decrease in pH values of the cement paste, resulting in the reinforcement depassivation. Once depassivated, the rebar is susceptible to corrosion process. Traditional repair method consists in removing the affected portion of concrete, substituting it for a new and alkaline concrete, generating construction waste and bringing problems to the safety of construction workers, residents, and pedestrians. Chemical and electrochemical realkalisation arise as nondestructive methods to the presented pathology. Electrochemical realkalisation consists in connecting a direct current power supply to the interior rebar and to the metallic mash on the outside, which is covered by an alkaline solution. The alkaline solution penetrates the concrete structure, while alkaline ions are generated around de interior rebar by electrolysis. Nowadays, electrochemical realkalisation is used as a prevention method to corrosion, before the carbonation front reaches the reinforcement. The present paper aims to study the influence of time and current density applied during the repair process on the efficiency of the ERA method. Mortar specimens were cast using the same mix and placed in a carbonation chamber. Absorption, compressive strength, carbonation depth, mercury intrusion porosimetry and thermogravimetric analysis tests were performed on three specimen groups: reference, carbonated and realkalised. It was concluded that the application of a current density of 0,5 A/m² for 7 days during the electrochemical realkalisation process was enough to reestablish the alkalinity os the specimens. Despite these results, the application of 1,5 A/m² for 14 days presented better changes in the mortar microstructure.